2017
DOI: 10.5847/wjem.j.1920-8642.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient tracking in earthquake emergency response in Iran: A qualitative study

Abstract: BACKGROUND:After a disaster, all victims have to be rapidly and accurately identified for locating, tracking and regulating them. The purpose of this study was to summarize people's experiences that how the patients were tracked in past earthquake disasters in Iran. METHODS:A qualitative study was carried out in 2015. This was an interview-based qualitative study using content analysis. The interviewed people included physicians, nurses, emergency medical technicians, disaster managers, Red Crescent Society' f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[21] Furthermore, studies have shown that paying attention to women's mental health improvement is one of their most important requirements during disasters. [14,15,24] The experts then prioritized some social dimensions that were specific to and suitable for women and recommended for them; the fact that women naturally need more social group support and show a more suitable performance in friendly and familiar relationships and groups. It has been illustrated in studies that social relationships protect women's mental health from earthquake damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] Furthermore, studies have shown that paying attention to women's mental health improvement is one of their most important requirements during disasters. [14,15,24] The experts then prioritized some social dimensions that were specific to and suitable for women and recommended for them; the fact that women naturally need more social group support and show a more suitable performance in friendly and familiar relationships and groups. It has been illustrated in studies that social relationships protect women's mental health from earthquake damage.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the importance of the establishment of specifi c policies and laws for preserving the mental health of women has been emphasized in studies. [5,9,14,26] Other factors that were in the next degree of importance, however with very little degree of difference to the previous ones, included psychological well-being through treatment of mental disorders (treatment of mental disorders including anxiety, depression, PTSD, fear of injury, shock, imagination of death and disaster, tendency toward self-harm, suicidal thoughts), dignity and position of women in situations of harm (social value of women in disasters, key role of women in the damaged family, role of women as levers in events, maternity role, the spouse role, women's participation in society), nutrition and physical activities during disasters (healthy nutrition, nutritional problems in crisis, preservation of food for emergencies, women's nutrition in certain physical conditions, suitable activities in less-equipped places, exercising in limited conditions, appropriate physical activities for physical damages), role and responsibilities of women in crisis (lack of abuse of women in multiple responsibilities, suitable attention to the simultaneous spouse-mother role of women, inconsistency between women's efforts and the outcomes, suitable participation of women in constructional development, overburden in difficult conditions), health-seeking behaviors during disasters (body care under damage conditions, making health claims, awareness of observance of health issues, feeling responsible for their own health and that of others, access to health services in special circumstances), awareness of high-risk behavioral habits (smoking, alcohol use under stress, risky sexual behaviors, drug abuse, coping with unsuitable behavioral habits in crisis), learning skills and gaining experiences (familiarity with incomegenerating jobs, training applied skills like tailoring, driving, building, swimming, carpet weaving, making handicrafts, dairying, and etc., self-help, learning how to provide for the family as a householder), and governing culture in the disaster area (respect for the culture of the region, cultural adaptation of the injured and helpers, cultural constraints of women, consideration of cultural indicators of women of the area when providing assistance, lack of priority of rescuing women due to the governing culture).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakness in patient tracing, reporting and information on the condition of patients, resulting from the absence of a specific protocol and operational program in this regard, were among the main challenges reported on the response by the health field in this event. In the study by Tavakoli et al (2017) the said problem was also one of the main findings of the study and it is necessary to address this problem in order to cope with future incidents [23].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] The current status of Iran's preparedness to deal with natural disasters in terms of identifying, locating, and tracking patients is representative of a wide gap in both emergency preparedness and health management in disasters. [ 12 ] Therefore, it is vital to develop an efficient tracking system to document patients’ conditions and locations from scene till evacuation and transfer to health-care centers, deployment in hospitals to proceed with treatment, and ultimately complication of the treatment course and discharge from health care system to prepare for and respond to disasters in Iran. [ 13 14 15 16 ] The aim of the present study was to develop a model of natural disaster patient tracking system for Iran.…”
Section: Introductionmentioning
confidence: 99%